Modelling of inductive coupling transducer for activation of low wattage electronic implants - Arshad, Atika; Khan, Sheroz; Tasnim, Rumana; Alam, A. H. M. Zahirul (2011)
A wireless power supply system based on inductive coupling approach has been developed for implantable biomedical devices that achieves excellent transducer performance by obviating the need for electrical connectors. In this paper, we report in detail the modeling and electrical analysis of an inductive power link for activation of microwatt electronic implants. As the biomedical application requires a safe and clean source of energy to power their operation, the implantable device sourced this power from an astable timer circuit in this system. The system is integrated with a 555 timer connected in astable mode, an inductive sensor, a receiver coil (represented by the secondary winding of transformer), a transmitter coil (represented by the primary winding of transformer) and a monitoring device.